Liberdade e determinação: para uma compreensão da relação entre liberdade e alienação a partir de o ser e o nada - Carvalho, Tiago de Oliveira (2020)
This dissertation intends to show how Sartre’s phenomenology achieves a concrete ontologi cal description of human experience. In others words, the analysis of the main existentialism notions is carried out in Being and nothingness in order to demonstrate that Sartre’s descrip tion cannot be equated with metaphysical discourses. Firstly, it aims to understand how the philosopher organizes his description based on the finding of the factual union between con sciousness and the world in such a way that it becomes possible to describe both the structures of being that are involved in the verified relationship and the way by which these ontological structures are linked. Secondly, affirming the concrete character of such a description makes it possible to argue in favor of the concreteness of the ambiguous relationship between freedom and situation by explaining how the description of human reality takes into account its his toricity. In the meantime, it is argued that the ambiguity of the freedom/situation relationship gives rise to an understanding of historical alienation’s problem that overcomes the antagonis tic impasse between freedom and determination. Finally, the essay Materialism and Revolu tion is analyzed in order to understand how Sartre structures a paradoxical understanding of the historical agent by defining him as a free and alienated being